On the Interaction between Trichogramma chilonis and Jatiroto Flies with Stem Borer Pests in Sugarcane Plantation - Fauzi, Rifky; Mufidah, Zunanik; Maretta, Gres; Edriani, Tiara Shofi; Rizka, Nela; Mukhaiyar, Utriweni; Utami, Riani; Haryani, Sri; Saefudin, Saefudin; Styaningrum, Amalia; Soewono, Edy (Directorate for Research and Community Services (LPPM) ITB, 2024)
Pests in sugarcane plantations are a major cause of damage, which could lead to severe damage to the crop, reduction of sugar quality, and significant economic loss. One of the major pests known in sugarcane plantations is stem borer (Chilo sacchriphagus), which attacks the canes. Two primary parasitoids, Trichogramma chilonis, which predates the stem borer eggs, and the Jatiroto fly (Diatraeophaga striatalis), which predates the stem borer larvae, are discussed here. This paper presents a time-dependent ten-dimensional dynamical mathematical model consisting of four-stage stem borer compartments, three-stage Trichogramma compartments, and three-stage Jatiroto compartments. Simulations are presented to describe the phenomenon of Trichogramma predation, Jatiroto predation, and simultaneous predation of both predators. It is shown that the release rate of each predator and a combined release of two predators can significantly reduce the infestation levels to a tolerable level for sugarcane production. The oscillatory dynamics of the stem borers and the Jatiroto flies affected the release timing strategy based on the level of infestation in the field. The results are expected to help us better understand the predator-prey phenomenon in the field and improve the forecasting of infestations in the field.